2002
DOI: 10.1590/s0034-70942002000500001
|View full text |Cite
|
Sign up to set email alerts
|

Influência do sevoflurano e do isoflurano na recuperação do bloqueio neuromuscular produzido pelo cisatracúrio

Abstract: The recovery from cisatracurium-induced neuromuscular block was longer during anesthesia with volatile agents as compared to propofol. The most pronounced effect was observed with sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
1
6
1
1
Order By: Relevance
“…[3639] The mechanism behind this interaction has still not been fully elucidated. Potentiation may occur due to several factors: effect of volatile agents on acetylcholine receptor channels; action on the central nervous system, causing reflex medullary depression and contributing to tone reduction with skeletal muscular relaxation; decreased postjunctional synaptic membrane sensitivity to depolarization caused by acetylcholine; and increased muscle blood flow, allowing a higher amount of NMB to reach the site of action.…”
Section: Discussionmentioning
confidence: 99%
“…[3639] The mechanism behind this interaction has still not been fully elucidated. Potentiation may occur due to several factors: effect of volatile agents on acetylcholine receptor channels; action on the central nervous system, causing reflex medullary depression and contributing to tone reduction with skeletal muscular relaxation; decreased postjunctional synaptic membrane sensitivity to depolarization caused by acetylcholine; and increased muscle blood flow, allowing a higher amount of NMB to reach the site of action.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have found a similar onset time (1.50 minutes) in children receiving 0.5 mg.kg -1 atracurium 27 . Recovery time (T ) is a comparison standard largely independent of neuromuscular blocker dose and is inversely correlated to drug metabolization 8, 28 . However, for a drug where redistribution plays a major role in recovery, this ratio (T ) may increase after high doses, serial doses or continuous infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have shown that volatile anesthetics potentiate neuromuscular blockers action, thus prolonging their duration. This phenomenon is not yet well understood, but some factors might be involved, such as an action on acetylcholine receptors, action on the central nervous system with reflex medullary depression, decreased post-junctional membrane sensitivity to acetylcholine-induced depolarization, or even increased muscle blood flow [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations